Folk beliefs in the military community of the Philippine Military Academy, Baguio City - Angiwan, Zipporah Santos (2006)
This study entitled "Folk Beliefs in the Military Community of The Philippine Military Academy, Baguio City", is a collection of folk beliefs gathered from the military community residing at and within the vicinity of the Philippine Military Academy. It also presents a discussion of these folk beliefs in the context of military life and a distinct "military culture". The information needed for the study was gathered through nine separate interviews with ten respondents from the various fields of specialization of the Armed Forces of the Philippines, chosen according to the requirements needed for the study. The methods used in the data gathering process were taken from E. Arsenio Manuel's Guide for the study of Philippine Folklore (1985) to ensure "folkloricity" and a proper system in handling the information for this study. A total of twenty-five(25) beliefs were documented, excluding variants of particular beliefs, categorized according to Michael Jones'(1967) classification for folk beliefs. Discussions and analyses were done in relation to premises given by Joseph Campbell on the origins and functions of myths, as well as Carl Jung's psychological theories on the role of folk beliefs in the human psyche. These folk beliefs serve to give insights not just into something called "military culture" as a whole, but of the human psyche within that culture as well. It is important to understand this, because on the whole, warfare as an art is not just limited to the battlefield, but more so to the daily struggle that is human life --Author's abstract.
Thesis (Bachelor of Arts in Communication) -- University of the Philippines Baguio, 2006.
Includes bibliographical references.
Keywords: Philippine Military Academy; Folklore -- Philippines -- Philippine Military Academy(Baguio City)